The aromatic cage in the active site of monoamine oxidase B: effect on the structural and electronic properties of bound benzylamine and p-nitrobenzylamine - ERDEM, SAFİYE (SPRINGER WIEN, 2007)
Computational studies using the ONIOM methods have been performed to probe the catalytic roles of tyrosine residues 398 and 435 which constitute the '' aromatic cage '' in the active site of MAO-B. The results presented here provide additional new insights into the interactions that take place on activation of the amine substrate by the aromatic cage residues in MAO-B catalysis and have relevance to the MAO-A catalytic mechanism.
Keywords: ONIOM calculations; neurotransmitter; FAD binding site; enzyme modeling; OXIDATION; MUTANT